Spinal Fusion in Pediatric Patients With Low Bone Density: Defining the Value of DXA. Issue 7 (20th August 2022) - Cohen, Lara L.; Berry, Jay G.; Ma, Nina S.; Cook, Danielle L.; Hedequist, Daniel J.; Karlin, Lawrence I.; Emans, John B.; Hresko, Michael Timothy; Snyder, Brian D.; Glotzbecker, Michael P.
Abstract : Background: Children with medical complexity are at increased risk of low bone mineral density (BMD) and complications after spinal fusion compared with idiopathic scoliosis patients. Our aim was to compare treatments and outcomes of children with medical complexity undergoing spinal fusion in those who had dual-energy x-ray absorptiometry (DXA) scans versus those who did not in an effort to standardize the workup of these patients before undergoing spinal surgery. Methods: We conducted a retrospective review of patients with low BMD who underwent spinal fusion at a tertiary care pediatric hospital between 2004 and 2016. We consulted with a pediatric endocrinologist to create standard definitions for low BMD to classify each subject. Regardless of DXA status, all patients were given a clinical diagnosis of osteoporosis [at least 2 long bone or 1 vertebral pathologic fracture(s)], osteopenia (stated on radiograph or by the physician), or clinically low bone density belonging to neither category. The last classification was used for patients whose clinicians had documented low bone density not meeting the criteria for osteoporosis or osteopenia. Fifty-nine patients met the criteria, and 314 were excluded for insufficient follow-up and/or not meeting a diagnosis definition. BMD Z -scores compare bone density ascertained by DXA to an age-matched and sex-matched average. Patients who had a DXA scan were also given a DXA diagnosis of low bone density (≤−2 SD), slightly low bone density (−1.0 to −1.9 SD), or neither (>−1.0 SD) based on the lowest BMD Z -score recorded. Results: Fifty-nine patients were analyzed. Fifty-four percent had at least 1 DXA scan preoperatively. Eighty-one percent of DXA patients received some form of treatment compared with 52% of non-DXA patients ( P =0.03). Conclusions: Patients referred for DXA scans were more likely to be treated for low BMD, although there is no standardized system in place to determine which patients should get scans. Our research highlights the need to implement clinical protocols to optimize bone health preoperatively. Level of Evidence: Level II—retrospective prognostic study.